Analysis of Payment System Digitalization in Achieving Rupiah Stability and Financial System Stability in Indonesia - Dea Dellia; Lia Nazliana Nasution; Wahyu Indah Sari (International Journal of Economics, Commerce, and Management, 2025)
The purpose of this study is to examine how the growth of digital payment systems has affected Indonesia's financial system and rupiah stability. More people are using digital payment methods like e-money, credit cards, debit cards, RTGS, and QRIS as a result of technical advancements. Additionally, Bank Indonesia still encourages the adoption of digital payment methods to speed up, secure, and streamline transactions. The Two Stage Least Squares (TSLS) method is used in this study's simultaneous regression model, which employs secondary data from 2020 to 2024. The findings indicate that while inflation has a positive but negligible impact on the exchange rate, the use of credit cards and RTGS has a considerable positive impact. In the meantime, debit cards and e-money significantly reduce inflation. Inflation is significantly reduced by QRIS and the exchange rate. In order to maintain Indonesia's economic stability, it is crucial to keep enhancing literacy and security when using digital payment methods.